2022
DOI: 10.3389/fenvs.2022.956824
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among institutional actors for sustainable economic development—Role of green policies, ecoprenuership, and green technological innovation

Abstract: This study conceptualizes the impact of Green Economy Policies, namely, green fiscal policy, green investment, and green jobs, on sustainable economic development through direct and serially mediated paths. Ecopreneurship and Green Technological Innovation have been perceived/recognized as potential mediators linking green economy policies to sustainable economic development. The conceptual model sheds light on the integrated role of two main actors—the government of the state and its market forces in moving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Some also focus on social norms and values affecting sustainable entrepreneurship (Alpsahin Cullen, 2021; Lin and Niu, 2018; Meek et al, 2010), whereas belief systems remain underexplored. In terms of formal institutions, Wang et al (2022) studied the effect of green (entrepreneurship) policy on sustainable development and Zhao et al (2021) the influence of government support on the performance of sustainable entrepreneurship. So far, little attention has been afforded to how business models evolve depending on the factors within their institutional environment (Peprah et al, 2022), even though it is suggested that individual business models are shaped within an institutional context, presenting rules that foster specific types or ways of offering products and services (Bocken et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some also focus on social norms and values affecting sustainable entrepreneurship (Alpsahin Cullen, 2021; Lin and Niu, 2018; Meek et al, 2010), whereas belief systems remain underexplored. In terms of formal institutions, Wang et al (2022) studied the effect of green (entrepreneurship) policy on sustainable development and Zhao et al (2021) the influence of government support on the performance of sustainable entrepreneurship. So far, little attention has been afforded to how business models evolve depending on the factors within their institutional environment (Peprah et al, 2022), even though it is suggested that individual business models are shaped within an institutional context, presenting rules that foster specific types or ways of offering products and services (Bocken et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The fundamental purpose of developing a GE is to harmonize the economy, society, and environment, which involves production distribution, environmental protection, education, science and technology, and public health policies and practices. STI bridges the economy, society, and environment [24] and can play a critical role in GE development across these three dimensions [25]. At the economic level, STI products, such as patents and reports, can provide the theoretical basis for developing low-energy consumption and high-efficiency products, leading to more efficient production methods, accelerating the transformation of industrial structures, and facilitating high-quality economic development.…”
Section: Study Areamentioning
confidence: 99%
“…The integration of Green technology with the UN's Sustainable Development Goals offers a distinctive prospect [21] to expedite advancements towards a more equitable [17,22], sustainable [23,24], and inclusive global [25] community [26,27]. By leveraging the inherent qualities of blockchain technology, such as transparency, traceability, and decentralization, it can enhance the ability to tackle urgent global concerns effectively.…”
Section: Introductionmentioning
confidence: 99%